(untitled) (Revista cientifica In Vestigium Ire, 2016)
Current global productivity schemes require not only that members of participating organizations providing the best of their powers to achieve world class standards that the concert business requires, but also, you should add the talent and dedication of each and each of its members to do so, to develop schemes that contribute to the integration of its participants is essential. It is in this vein it is important to identify the symbols of power, as these symbols may serve to unify or to divide the different social groups within organizations. In order to identify the symbols of power in the selected organizations Queretaro State an instrument that is both reliable and valid for identification is used. The results of this research will contribute to the formulation of basic strategies for companies to achieve the much-desired productivity while promoting change business paradigms that exist largely today, seeking to provide tools for self-directed work teams. This research is not experimental, transactional, descriptive subjects using a sample of 130 type companies.